Implementasi Otonomi Khusus di Provinsi Aceh Berdasarkan Undang-Undang Nomor 11 Tahun 2006 - Husni Jalil; Teuku Ahmad Yani; Mohd. Daud Yoesoef (Kanun Jurnal Ilmu Hukum, 2010)
ABSTRACT: This research is to investigate and evaluate the implementation of special autonomy as it is regulated in the act No. 11, 2006 on the Government of Aceh. Data far this research was gathered by library resources, such as primary, second, tertiary law resources. Field study by interviewing some parties who were related this research was done in order to support secondary resources. The research findings show that the special autonomy in Aceh did not effectively implementation yet, this factor was caused by procedures of implementation (peraturan pelaksanaan) was not fulfilled by the center government. Special Autonomy Implementation in Province Aceh based on the act Number 11 of 2006